Parsing complex - compound sentences with an extension of Vietnamese link parser combined with discourse segmenter - Hương, Nguyễn Thị Thu; Hải, Nguyễn Thúc; Thủy, Nguyễn Thanh (Journal of Computer Science and Cybernetics, 2012)
Link grammar is a theory of syntax which builds relations between pairs of words, rather than constructing constituents in a tree-like hierarchy. Link grammar is similar to dependency grammar, but dependency grammar includes a head-dependent relationship, as well as lacking directionality in the relations between words. A link parser has been built for Vietnamese with acceptable results. In this paper, we propose an extended link parser with a new function to parse complex, compound and complex - compound sentences, except sentences with nested clauses. Sentences are segmented into clauses using discourse segmentation algorithm of sentence level. Parsing clauses separately is useful for coordination disambiguating and decreasing time complexity